Quarry dust as river sand replacement in cement masonry blocks: Eﬀect on mechanical and durability characteristics - Kosalya, S.; Arvinthan, P.; Anburuvel, A.; Sathiparan, N. (Elsevier, 2022)
Natural sand or river sand constitutes as major ﬁne aggregate in cementitious construction. Especially, masonry block production requires 70–90% sand as raw material. While the demand for river sand increases the supply of good quality river sand is limited due to the restrictions in sand mining in river beds. Because excessive extraction of river sand to cater the increasing demand has brought undesirable environment-related consequences. The persisting issues encouraged the researchers to ﬁnd a sustainable alternative for river sand. Quarry dust is one of the alternatives as it has some advantages over river sand such as better contribution to the strength of the cementitious material, better workability, lesser cement consumption and eco-friendly. The present study explored the feasibility of using quarry dust as ﬁne aggregate in manufacturing cement blocks. Cement blocks with four diﬀerent quarry dust composition levels 0, 33.3%, 66.7 and 100%, were prepared and tested. The testing included determination of mechanical characteristics (compressive and ﬂexural strength) and durability aspects (sorption, evaporation, wet and dry cycle, resistance against salt, alkaline and acid solution)The test results exhibited that mechanical characteristics and resistance against wet and dry cycles improved when quarry dust completely replaced river sand as ﬁne aggregate. When quarry dust content increased, the cubes subjected to severe environmental conditions exhibited higher strength reduction rates compared to that of normal environmental condition. The ﬁnal strength, however was higher than the corresponding cubes with river sand. In addition to strength improvement, quarry dust replacement yielded lesser cost and sustainable beneﬁts, which would promote the deployment of quarry dust in cement-sand block production.
Keywords: Cement blocks; River sand; Quarry dust; Strength; Durability